Pessoas com deficiência e esporte adaptado: a questão da inclusão e da inserção social - Vargas, Leandro Silva (Universidade do Vale do Rio dos Sinos, 2011)
This paper is the product of research work carried out with three groups that practice adapted sports on a regular basis. From an ethnographic standpoint, it discusses the relationship adapted sports and people with a disability have with the institutions that offer such sports. We looked into the types of sport activities the institutions offer, their benefits, how they take place, and what people?s access to these institutions is like. This investigation sought to identify the different ways the work carried out by the groups offering adapted sport activities is seen both by the institutions and the community (of participants). Our research also addresses the issue of accessibility in the streets, public transportation and even inside the institutions. Additionally, it shows how important families are to ensure participants keep on practicing adapted sports, and what the medias role has been. The latter has been giving visibility to athletes with a disability only when there are competitions, like the Parapan and the Paralympics, which furthers the discussion about the inclusion of people with a disability.
Keywords: Esporte adaptado; Pessoa com deficiência; Inclusão social; Adapted sports; People with a disability; Social inclusion; ACCNPQ::Ciências Humanas::Sociologia